2006
DOI: 10.1136/thx.2006.059071
|View full text |Cite
|
Sign up to set email alerts
|

Smokers with airway obstruction are more likely to quit smoking

Abstract: Background: Chronic obstructive pulmonary disease (COPD), usually caused by tobacco smoking, is one of the leading causes of morbidity and mortality. Smoking cessation at an early stage of the disease usually stops further progression. A study was undertaken to determine if diagnosis of airway obstruction was associated with subsequent success in smoking cessation, as advised by a physician. Methods: 4494 current smokers (57.4% men) with a history of at least 10 pack-years of smoking were recruited from 100 00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
2
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 36 publications
6
94
2
7
Order By: Relevance
“…The increased smoking prevalence among men below age 65 years with COPD is interesting because it is not consistent with previous studies where patients with COPD were more likely to cease smoking compared with smokers in the general population [30,31]. The general prevalence of mild COPD at younger ages may have increased during the last decade due to higher awareness of the need to perform spirometry, and in this group of patients the rate of smoking cessation is lower [32].…”
Section: Discussionmentioning
confidence: 55%
“…The increased smoking prevalence among men below age 65 years with COPD is interesting because it is not consistent with previous studies where patients with COPD were more likely to cease smoking compared with smokers in the general population [30,31]. The general prevalence of mild COPD at younger ages may have increased during the last decade due to higher awareness of the need to perform spirometry, and in this group of patients the rate of smoking cessation is lower [32].…”
Section: Discussionmentioning
confidence: 55%
“…25 For mild patients who remain undiagnosed, some argue that early detection and prevention -particularly in introducing smoking cessation programmes -may offer a better long-term prognosis 26,27 although other studies have not confirmed this. 28,29 Also, although only five European countries were represented in this analysis and there were some inter-country variations in demographic factors, the relationship between HRQL impairment and PCP-rated severity showed very similar patterns across countries, suggesting that these data may be representative at the European level. This requires confirmation in further studies, with representation in Northern and Eastern Europe.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 93%
“…This argues strongly for the routine use of spirometry in smokers to identify those with COPD and those with a significantly elevated risk for lung cancer, both of which have previously been shown to assist in smoking cessation [30][31][32].…”
Section: Thoracic Oncology Rp Young Et Almentioning
confidence: 99%
“…We believe that, just as it is important to measure and document blood pressure (for risk of future stroke), bone mineral density (for risk of future fractures) or BMI (for risk of future diabetes), lung function should be measured and recorded for assessing the risk of future lung cancer [10,[13][14][15]34]. The assessment of lung cancer risk and the utility of measuring lung function have potential clinical benefits in smoking cessation [30][31][32] and targeted CT screening [35]. There may also be utility in the early diagnosis of lung cancer where delays in the diagnosis [16], tumour size and mortality are closely related [36].…”
Section: Thoracic Oncology Rp Young Et Almentioning
confidence: 99%